Karakteristik Morfologi dan Hasil Kedelai Edamame yang Diberi Eco-enzyme dan Pengendalian Gulma Berbeda di Lahan Tropis - Soverda, Nerty; Swari, Elly Indra; Neliyati, Neliyati; Ratna, Yuni; Pebrianti, Herni Dwinta; Wahyuni, Dilla (Universitas Batanghari, 2024)
Edamame soybeans are a variety of soybeans that act as leaf vegetables that are rich in protein, minerals and vitamins. Edamame soybean cultivation is not yet popular, even though the need and demand is quite large. Eco-enzymes are inputs that play an important role as natural hormones and provide nutrients for plants. Eco-enzyme is an organic product that goes through an anaerobic fermentation process. A decrease in the yield of cultivated plants can be caused by competition with weeds. Several general weed control options have been developed, but appropriate weed control options are needed to ensure production and ecological sustainability. Research was carried out at the Teaching and Research Farm (1Â°370'129